Autoimmune cerebellar ataxia with anti-Homer3 antibodies associated with herpesvirus infection: a case report and literature review - Song, De-Jin; Dong, Ran; Liu, Yi-Ming; Wang, Tan; Ma, Jun (Frontiers in Immunology, 2026)
Autoimmune cerebellar ataxia (ACA) is a cerebellar syndrome mediated by autoimmune mechanisms. ACA is particularly rare, and cases of ACA with anti-Homer-3 antibodies associated with herpesvirus infection are even rarer. In this study, we report a case of a 15-year-old girl who was admitted with a one-month history of progressive vertigo and unsteady gait. Metagenomic next-generation sequencing (mNGS) of her cerebrospinal fluid (CSF) revealed eight sequences of human herpesvirus 7 (HHV-7). Anti-Homer-3 antibodies were detected in both serum and CSF samples. Following a series of immunotherapy, the patient showed improvements in dizziness and gait stability. However, her symptoms recurred during the tapering of corticosteroids. The patient developed three episodes of generalized seizures. Concurrently, gait instability significantly worsened. Repeat first-line immunotherapies including corticosteroid and IVIG were not effective. Rituximab was initiated and symptoms were partial improved. In this study, we present the clinical symptoms of this patient with anti-Homer-3 antibody-associated ACA, conduct long-term follow-up, and review relevant literature. Our aim is to enhance the understanding of this rare disease by summarizing key clinical features, thus providing valuable insights into the diagnosis and treatment of ACA.